2018
DOI: 10.3332/ecancer.2018.844
|View full text |Cite
|
Sign up to set email alerts
|

The presence of secondary circulating prostate tumour cells determines the risk of biochemical relapse for patients with low- and intermediate-risk prostate cancer who are treated only with external radiotherapy

Abstract: IntroductionThe classification of patients with prostate cancer is used to determine treatments based on risk factors. The presence of secondary circulating prostate tumour cells (CPCs) detected in peripheral blood after a curative treatment has been associated with a worse prognosis. We present a prospective study of CPC detection post radiotherapy and the oncological results.Patients and methodsAll of the patients classified as low and intermediate risk that were treated with radiotherapy were included. Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the latter study did not perform a longitudinal follow-up of localized PCa patients for further prognostic evaluation [53]. Murray et al took a different approach by using density gradient isolation and detection of CTC by PSA immunocytochemistry on a large cohort of localized PCa patients [59]. Importantly, the authors reported a significant correlation between CTC detection and clinical variables such as PFS after a long follow-up period of 15 years.…”
Section: Ctc Detection In Non-metastatic Prostate Cancermentioning
confidence: 99%
“…However, the latter study did not perform a longitudinal follow-up of localized PCa patients for further prognostic evaluation [53]. Murray et al took a different approach by using density gradient isolation and detection of CTC by PSA immunocytochemistry on a large cohort of localized PCa patients [59]. Importantly, the authors reported a significant correlation between CTC detection and clinical variables such as PFS after a long follow-up period of 15 years.…”
Section: Ctc Detection In Non-metastatic Prostate Cancermentioning
confidence: 99%
“…Thus, in the study by Miyamoto et al [ 112 ], isolated from blood CTCs were investigated via whole transcriptome amplification, which allowed to predict dissemination of the CTCs to seminal vesicles and lymph nodes In a cohort of patients at 34 subjects. Another approach for label-free isolation of PCa CTCs, gel centrifugation, was proposed by Murray et al [ 113 ]. Notably, in this study, blood was collected from patients at 3 months post-radiotherapy.…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%